A4NH 2020 annual report highlights: Flagship 2 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2021)
This includes three highlights document for Flagship 2 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: New research shows nutritional efficacy and effectiveness Highlight 2: Reaching farmers in times of crisis Highlight 2: Reaching farmers in times of crisis